Psikologi Kepribadian dalam Pendidikan di Sekolah - Sukatin Sukatin; Helen Fasya Sabrina; Khrysma Septiana; Nur Aisyah; Nur Hafizi (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Personality psychology is psychology that specifically describes the structure of the human person, regarding the types of human personality. Personality psychology is one of the special and very important parts or characteristics for human life. Therefore personality psychology is a very important thing to study. Personality psychology, like other branches of psychology, makes a valuable contribution to the understanding of human beings through the scientific framework of psychology. What distinguishes personality psychology from other branches of psychology is its attempt to synthesize and integrate the principles contained in these other fields of psychology. In the field of psychology there is no single field that has such a broad area as personality psychology. Psychology of personality in education in schools is scientific knowledge about the nature or character of a person in the educational aspect or more specifically the character and nature of students, where a teacher can know and understand the character and characteristics of his students in order to achieve an optimal learning.